2013
DOI: 10.1016/j.juro.2012.08.195
|View full text |Cite
|
Sign up to set email alerts
|

Prebiopsy Magnetic Resonance Imaging and Prostate Cancer Detection: Comparison of Random and Targeted Biopsies

Abstract: When performed with computerized magnetic resonance imaging-transrectal ultrasound image registration, targeted biopsy alone improved cancer detection over random biopsies, decreased the detection rate of microfocal cancer and increased the detection rate of cancer with a Gleason score of greater than 6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
164
2
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(188 citation statements)
references
References 21 publications
14
164
2
8
Order By: Relevance
“…A total of 8663 original studies in English were identified and 15 were analyzed. [2][3][4][6][7][8][23][24][25][26][27][28][29][30][31] The overall quality varied from low to moderate. Fourteen conference abstracts will require followup in future updated versions.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 8663 original studies in English were identified and 15 were analyzed. [2][3][4][6][7][8][23][24][25][26][27][28][29][30][31] The overall quality varied from low to moderate. Fourteen conference abstracts will require followup in future updated versions.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…• Eight eligible studies 2,3,6,7,[23][24][25][26] addressed the first objective. The quality of evidence ranged from poor to moderate.…”
Section: Key Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11][12] Targeted biopsy of MP-MRI lesions can be performed directly using MRI [8][9][10] or under ultrasound guidance using cognitive targeting or MRI-TRUS fusion software. 6,13 Needle insertion can be transrectal or transperineal under ultrasound guidance.…”
Section: Introductionmentioning
confidence: 99%
“…For performing the fusion between the two volumes, elastic systems take into consideration prostate movements and deformation during the insertion of the US probe, whereas rigid systems relay only on internal anatomical markers [49]. Delongchamps et al [50] showed that elastic image fusion was more accurate for cancer detection than rigid image fusion, which performed similarly with cognitive guided biopsy [51].…”
Section: Ultrasound-mri-guided Prostate Biopsymentioning
confidence: 99%